التنوع الثقافي في الجزائر من خلال الأزياء التقليدية: مقاربة سوسيو- أنثروبولوجية لمجموعة متحفية تابعة للمركز التفسيري للباس التقليدي: Cultural diversity in Algeria through traditional costumes: a socio-anthropological approach to a museum collection belonging to the Interpretive Center for Traditional Dress - خيذر جميلة; دحماني سليمان (Maalim, 2021)
Through this research paper, we seek to highlight one aspect of cultural diversity in Algeria, which is the diversity of traditional costumes that differ from one region to another, and this is through a socio-anthropological study of a museum group affiliated with the Interpretive Center for Traditional Dress, located in the Royal Ziani palace in Tlemcen. This study found that the traditional costumes reflected to a large extent the local and subcultures that distinguish one region from others in Algeria, as well as social classes, and the popular beliefs and rituals. The study also found that part of this authentic heritage has been neglected and extint as a result of the political, economic and social changes that algerian society has witnessed since the french entry in 1830.